Development of Game Media „Onet Familie“ to Practice Mastery of German Vocabulary for 11th Grade Students at SMA Negeri 1 Tumpang - Dhea Widia Putri; Sawitri Retnantiti (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2022)
This R&D aims to develop the Onet Familie media game with the theme Familie to train the mastery of German vocabulary for 11th Grade Students at SMA Negeri 1 Tumpang. Onet Familie contains practice questions about vocabulary articles and pictures about family. The model used in this development is a four-D model that has been modified in three stages, namely: (1) Define (definition), (2) Design (planning), and (3) Develop (development). Results of the product validation and testing analyzed descriptively quantitatively with the following results: (a) The validity of the material according to the material expert is 63 percent, (b) The validity of the media according to the media expert is 90.7 percent, and the response of students as test respondents is 81.7 percent. On average, students can complete the practice questions in the Onet Family game media at level 1, 2 and 3 well. Based on the product validity criteria used in this development, the Onet Familie game media is included in the very feasible category, so it can be used as an alternative in learning German vocabulary in class XI SMA.